2001
DOI: 10.1080/00288330.2001.9517045
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth, and sexual maturity of two New Zealand endemic skates,Dipturus nasutusandD. innominatus

Abstract: Rough and smooth skates (Dipturus nasutus (Banks 1841) and/), innominatus (Garrick & Paul 1974)) were aged by counting growth bands on X-rays of thick sections of vertebral centra. Band counts were imprecise, but there was no betweenreader bias. Age estimates were not validated. The oldest rough skate was 9 years old, but few were more than 6 years old. Females may live longer than males. The combined sexes von Bertalanffy growth curve was L r = 91.3 (1 -e -0.16 [ t + 1.20 ]). Half the males matured by c. 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
38
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 25 publications
11
38
0
3
Order By: Relevance
“…Historically, studying the reproductive biology of elasmobranchs entailed sacrificing a relatively large number of specimens and observing the changes in gross reproductive morphology over the reproductive cycle (e.g., Hisaw and Albert 1947;Zeiner and Wolf 1993;Walmsley-Hart et al 1999;Francis et al 2001;Ebert 2005;Ruocco et al 2006). While this approach is still currently appropriate for elasmobranchs with sustainable population sizes (Heupel and Simpfendorfer 2010), it is not suitable for many because of their relatively low or unknown species abundance (IUCN 2011;Hammerschlag and Sulikowski 2011).…”
mentioning
confidence: 99%
“…Historically, studying the reproductive biology of elasmobranchs entailed sacrificing a relatively large number of specimens and observing the changes in gross reproductive morphology over the reproductive cycle (e.g., Hisaw and Albert 1947;Zeiner and Wolf 1993;Walmsley-Hart et al 1999;Francis et al 2001;Ebert 2005;Ruocco et al 2006). While this approach is still currently appropriate for elasmobranchs with sustainable population sizes (Heupel and Simpfendorfer 2010), it is not suitable for many because of their relatively low or unknown species abundance (IUCN 2011;Hammerschlag and Sulikowski 2011).…”
mentioning
confidence: 99%
“…Several factors have been used to estimate female maturation in elasmobranch species, including ovary weight (OW; Walmsley-Hart et al 1999;Mollet et al 2000), cloacal length (Sosebee 2005), oocyte stage or size (Fitz and Daiber 1963;Richards et al 1963;Johnson 1979;Mollet et al 2000;Francis et al 2001;Conrath and Musick 2002), histological staging, and steroid levels (Sulikowski et al 2005). Here we examine the reproductive patterns in little skate and winter skate as defined by OW and oocyte stage, using specimens collected during the spring and fall of 1999 and during all seasons of 2001-2002 in the western Atlantic from Cape Hatteras, North Carolina, to Canadian waters.…”
mentioning
confidence: 99%
“…A variety of mineralised structures may be used for age and growth estimation in chondrichthyans, i.e., vertebrae (Francis et al, 2001;Gedamke et al, 2005;Ainsley et al, 2014;Natanson et al, 2014), dermal denticles (Moura et al, 2004;Campana et al, 2006;Serra-Pereira et al, 2008), and caudal thorns (Henderson et al, 2004;Francis & Ó Maolagáin, 2005;Arkhipkin et al, 2008;Francis & Gallagher, 2009). A popular ageing technique in elasmobranch is the sagittal-sectioning of vertebral centra from the thoracic region (Cailliet et al, 2006).…”
Section: Age Growth and Longevitymentioning
confidence: 99%
“…Intense local fisheries with unmanaged landings are often accompanied by a lack of biological information required to maintain a healthy fishing stock (Ferretti et al, 2008(Ferretti et al, , 2010, and it has been suggested that longnose skates are generally vulnerable to stock collapse even when subjected to low levels of fishing pressure (Agnew et al, 2000). (Casey & Myer, 1998;Francis et al, 2001;Dulvy et al, 2008;Dulvy & Forrest, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation